The Swedish microchipping phenomenon - Petersén, Moa (Emerald points., 2019)
This book is an investigation of the Swedish microchipping phenomenon and seeks to explain why, despite its many negative connotations in an international context, microchipping is relatively popular in Sweden. The author maps out the movement, examines its key drivers, and delves further to discover why Swedes generally have a high trust in technology, and show little resistance to testing it. The Swedish case is studied from the three main themes of surveillance, science fiction and transhumanism, and is built around interviews with Swedes who have embraced the technology. The arguments for and against microchipping are contextualised culturally and explained against a background of the long established Swedish relationship with advanced technology, and with their unique level of trust in the government. The book will be of interest to undergraduate and graduate students in digital culture related disciplines.